Speculative Criminality at Home: Bypassing Tenant Rights Through Police Surveillance in Detroit’s Rental Housing - Rae Baker (Urban Planning)
In 2016, Detroit, Michigan’s police department piloted a city-wide public-private-community video surveillance program called Project Green Light (PGL). Businesses that host the service, typically gas stations and convenience stores, receive priority response times for emergency dispatch calls, artificially decreasing 911 response times in a city with historically low emergency response capacity. This has led to many senior care homes with medically vulnerable residents to subscribe to PGL, as well as landlords of residential apartment buildings. While the program has been identified as a marker of gentrification by housing and anti-surveillance activists and residents, it has also raised concern about perpetuating the criminalization of Black Detroiters, specifically those living in rental housing that hosts the technology. In a city that is rapidly evolving through private, institutional, and public partnership developments while elected officials espouse to maintain racial and economic equity as core values of Detroit’s upcoming master planning process, the lack of foresight of the impact of surveillance tech is striking. The article’s focus is on surveillance technology as a defining element of contemporary urban development which enacts both a forbearance and expansion of rights through the application of technology to property relations. Relying on the automation of policing and racially biased artificial intelligence perpetuates criminality based on race, class, and perceived gender while additionally tying those experiences to the bundle of rights associated with the ownership of property.